FIRST-PRINCIPLES STUDY OF BaFe2-xNixAs2 (x=0,0.125,0.25, q And 2) SUPERCONDUCTOR USING DENSITY FUNCTIIONAL THEORY - Kamaliati Hanum Kamaruddin (Tesis, 2022)
The aim of this study is to verify electronic features contributed to Fe-SC. This is done by calculating various electronic phase properties of BaFe2-xNixAs2 using Density Functional Theory (DFT).